Unveiling the Impact of Psychological Factors on Consumer Purchase Intentions for Overall Sustainable Success in Green Residential Buildings: Using SEM-ANN Analysis - Ahmad M. Zamil; Ahmed Farouk Kineber; Mohammad Alhusban (Salehan Institute of Higher Education, 2024)
The research problem addressed in this study is the limited understanding of the intricate interactions among emotional, environmental, and psychological factors within organizations and their collective impact on overall sustainable success (OSS). A critical gap exists in the literature, as previous studies often analyze these factors in isolation, leaving an incomplete picture of their interdependence. To fill this gap, this study aims to comprehensively understand the interplay between Psychological Factors (PF) and OSS. The objectives are to identify relevant factors, collect data, and employ a rigorous methodology for analysis. The research methodology involves a three-phase approach: factor identification, data collection, and analysis. This study leverages a unique integration of Structural Equation Modeling (SEM) and Artificial Neural Networks (ANN) to deepen the analysis, revealing intricate relationships among identified factors. The study's findings highlight a robust positive association between PF and OSS, underscoring the significance of prioritizing employees' psychological well-being for enhanced workplace satisfaction and performance. These insights have practical implications for organizational leaders and managers, guiding them to cultivate positive emotional climates, instill environmentally conscious practices, and address negative emotional states within their teams. Doi: 10.28991/CEJ-2024-010-05-07 Full Text: PDF